2023
DOI: 10.5603/cj.a2022.0116
|View full text |Cite
|
Sign up to set email alerts
|

Medical therapy with flecainide and propafenone in atrial fibrillation: Long-term clinical experience in the tertiary care setting

Abstract: This article has been peer reviewed and published immediately upon acceptance.It is an open access article, which means that it can be downloaded, printed, and distributed freely, provided the work is properly cited. Articles in "Cardiology Journal" are listed in PubMed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…PROP is a class 1c antiarrhythmic drug that blocks the Na+ current and is used to control heart rhythm in patients with atrial fibrillation [25]. The present study is one of the few found in the literature reporting the activity of PROP against strains of Candida spp.…”
Section: Discussionmentioning
confidence: 88%
“…PROP is a class 1c antiarrhythmic drug that blocks the Na+ current and is used to control heart rhythm in patients with atrial fibrillation [25]. The present study is one of the few found in the literature reporting the activity of PROP against strains of Candida spp.…”
Section: Discussionmentioning
confidence: 88%
“…Similar to AF treatment, the drugs of first choice for maintaining sinus rhythm are antiarrhythmic class IC, in the absence of structural heart disease, or class III if it is present [ 51 ]. Special caution should be taken with the administration of antiarrhythmic drugs from the IC group, up to 25% may develop typical atrial flutter [ 70 ]. Flecainide and propafenone can slow conduction through atrial tissue more than they prolong refractoriness.…”
Section: Treatmentmentioning
confidence: 99%
“…This condition is known as class IC atrial flutter. Characteristically, its cycle length is greater than spontaneous typical flutter and it can lead 1:1 atrioventricular conduction and thus a significant increase in ventricular response, potentially causing hemodynamic compromise or even ventricular fibrillation [ 70 , 71 ]. Consequently, it is usually recommended to prescribe AV nodal-blocking agents in addition to class IC drugs to reduce this potential risk [ 70 ].…”
Section: Treatmentmentioning
confidence: 99%
“…Zhender et al [8] observed nausea and vomiting at short-term higher therapeutic doses and the exacerbation of ventricular extrasystoles during long-term treatment. Various studies also describe a proarrhythmic adverse effect, such as wide complex tachycardia or QRS broadening [9]; electrocardiogram-associated adverse events (prolonged QRS and QTc, first-and second-degree atrioventricular nodal block, bradycardia); and systematic adverse events (hypotension, dizziness, dysgeusia, fatigue, irritation and gastrointestinal intolerance) [10]. The coadministration of metoprolol and verapamil also increases the risk of toxicity [11,12].…”
Section: Introductionmentioning
confidence: 99%